A meta-frontier approach to measuring technical efficiency and technology gaps in beef cattle production in Argentina - Lema, Rolando Daniel; Gatti, Nicolas; Brescia, Victor (2018)
In this paper the stochastic metafrontier method is applied to estimate technical efficiency (TE) and metatechnology ratios (MTR), in beef cattle production for three distinct regions in Argentina. A deterministic stochastic metafrontier production function model is estimated that envelops the individual stochastic frontiers of the three regions. Our results show that firms from Pampean region, the most favored in terms of environment conditions, have an average (TE) of 53.7per cent, meanwhile for others regions the TE is around 58.966.97per cent. The average MTR for Pampean region is 96.8per cent, in contrast, the others regions have an average MTR of 42per cent. Our results suggest that, farms in the Pampean region could improve their performance through a better management using the available technologies and resources. In regions II and III the improvement of the productivity is likely to require additional investment in research to adapt and develop new technologies.